PHITOPLANKTON DIVERSITY IN KAMPAR VILLAGE RIVER KUALA TERUSAN SUB-DISTRICT PANGKALAN KERINCI PELALAWAN DISTRICT - Puspita, Rita; Adriman, Adriman; Fajri, Nur El (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPhytoplankton can act as one of the ecological parameters that can describe the condition of the water. This research was conducted in the Kampar River in Kuala Terusan Village in June-August 2019. The research was conducted at three stations. Sampling was carried out three times in one week intervals. Water quality parameters measured during the study are temperature, brightness, current speed, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Types of phytoplankton in the Kampar River Kuala Terusan Village 27 types are consisting of 3 classes, namely: Bacillariophyceae (2 types), Chlorophyceae (15 types) and Cyanophyceae (10 types). The abundance of phytoplankton species in the Kampar River in the Kuala Terusan Village ranges from 2914 - 7818 cells / L. The results of the phytoplankton species diversity index (H ') in the Kampar River Kuala Terusan Village ranged from 2.4906 to 2.7727, the uniformity index (E) ranged from 0.6093 to 0.6784, the dominance index (C) ranged from 0.1886 to 0,2616. The water quality of the aquatic environment in the Kampar River in Kuala Terusan Village is as follows: temperature 29-30˚C, pH 5, current speed 0.16-0.24 m / sec, brightness 24-37 cm, dissolved oxygen 3.2-4, 6 mg / L, free carbon dioxide 3.1-3.8 mg / L, nitrate 0.1855-0.2152 mg / L, and phosphate 0.0726-0.1195 mg / L. Keywords: Phytoplankton, Kampar River, diversity